Tarbiyatul Aulad : Pendidikan anak dalam islam / Abdullah Nashih Ulwan; Penerjemah, Emiel Ahmad; Mansyur Alkatiri dan Yanto Musthofa - ULWAN Abdullah Nashin; EMIEL Ahmad; MANSYUR Alkatiri; YANTO Musthofa (Khatulistiwa Press, 2013)
638 hlm. ; 26cm.